OPTIMIZATION OF ULTRASOUND-ASSISTED EXTRACTION CONDITIONS OF ANTIOXIDATIVE COMPONENTS FROM ARUNDINA GRAMINIFOLIA BY RESPONSE SURFACE METHODOLOGY BASED ON DPPH RADICAL SCAVENGING ASSAY - X. F. Li; Y. T. Gao; X. X. Pang; X. F. Liu; W. Y. Li; Y. L. Zhang; B. Y. Fan (Journal of Animal and Plant Sciences, 2015)
Response surface methodology(RSM) was employed to optimize conditions for ultrasound-assisted extraction(UAE) of antioxidantive components from Arundinagraminifolia. 1,1-diphenyl-2-picryl-hydrazyl(DPPH) free radical scavenging assay was used to evaluate the activity of antioxidative components. Based on the single-factor test, we identified extraction time, ethanol volume fraction, extraction temperature and liquid-solid ratio as the main variables that influence DPPH free radical scavenging activity of A. graminifolia extract. The optimal conditions to achieve the maximum activity were determined as follows: extraction time 35 min, extraction temperature46ºC, ethanol volume fraction 74%and liquid-solidratio27 mL.g -1 . The scavenging rateof 78.71%was achieved under the optimal extraction conditions, which was well in agreement with the optimal predicted values (79.16%). This extraction method was simple and efficient and provided a method of sample preparation to determine DPPH radical scavenging activity of total antioxidative components from A. graminifolia. The research also provided a reference for full utilization of A. graminifolia and identified a technique to extract antioxidative components.
Keywords: Arundinagraminifolia; antioxidative components; ultrasound-assisted extraction; response surface methodology; DPPH radical scavenging gassay